2011
DOI: 10.1016/j.vaccine.2011.05.031
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind trial to evaluate immunogenicity and safety of 13-valent pneumococcal conjugate vaccine given concomitantly with trivalent influenza vaccine in adults aged ≥65 years

Abstract: This randomized, double-blind study evaluated concomitant administration of 13-valent pneumococcal conjugate vaccine (PCV13) and trivalent inactivated influenza vaccine (TIV) in adults aged ≥65 years who were naïve to 23-valent pneumococcal polysaccharide vaccine. Patients (N=1160) were randomized 1:1 to receive PCV13+TIV followed by placebo, or Placebo+TIV followed by PCV13 at 0 and 1 months, with blood draws at 0, 1, and 2 months. Slightly lower pneumococcal serotype-specific anticapsular polysaccharide immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 16 publications
3
78
1
7
Order By: Relevance
“…Although there is no correlate of protection for the LLOQ defined in adults, the proportion of subjects achieving an OPA titer of ՆLLOQ after concomitant PCV13 and TIV was similar to or lower than that with PCV13 given alone, with two serotypes being statistically significantly lower after concomitant PCV13 and TIV. Lower IgG responses after concomitant PCV13 and TIV were also reported in a similarly designed study in Germany in adults of Ն65 years of age (20).…”
Section: Discussionsupporting
confidence: 72%
“…Although there is no correlate of protection for the LLOQ defined in adults, the proportion of subjects achieving an OPA titer of ՆLLOQ after concomitant PCV13 and TIV was similar to or lower than that with PCV13 given alone, with two serotypes being statistically significantly lower after concomitant PCV13 and TIV. Lower IgG responses after concomitant PCV13 and TIV were also reported in a similarly designed study in Germany in adults of Ն65 years of age (20).…”
Section: Discussionsupporting
confidence: 72%
“…In the three evaluated RCTs [23,82,83], those vaccinated with PCV13 reported muscle pain and local pain significantly more often (GRADE: "moderate" quality of evidence). Fever, malaise, headache, muscle and joint pain occurred more frequently among those vaccinated with PCV13, but the differences were not (or not in all three studies) significant (GRADE: "low" and "moderate" quality of evidence, respectively.…”
Section: Pcv13 (+Iiv) Vs Placebo (+Iiv)mentioning
confidence: 99%
“…13 Studies of antibody responses and duration following HPV vaccination have shown a maximum peak in antibody titers 7 months after beginning the vaccination scheme. 14,15 Subsequently, a gradual decline in antibody levels is observed, and by the 24 th month these levels stabilize and remain constant until at least the 60 th month. 16 To date, the minimum level of antibodies correlated with clinical protection is not yet known, 17 but a correlation has been established between the presence of antibodies and a protective effect.…”
Section: Introductionmentioning
confidence: 99%